1995
DOI: 10.1007/bf00887823
|View full text |Cite
|
Sign up to set email alerts
|

The significance of three-dimensional MR-defined neurovascular compression for the pathogenesis of trigeminal neuralgia

Abstract: Three-dimensional MR tomography was used to examine the relationship between symptoms of trigeminal neuralgia and neurovascular compression of the nerve in 18 patients. The intensity of neurovascular interaction was classified according to neuroradiological criteria. We found that a radiologically defined compression or dislocation of the nerve by an artery was always associated with symptoms of trigeminal neuralgia. A simple contact between vessel and nerve, however, was also observed on the asymptomatic side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 10 publications
1
24
1
3
Order By: Relevance
“…At operation, Tew et al [60] found a "significant" impingement in less than half of 50 patients in whom preoperative study showed arterial loop and neurovascular contact. Fortunately, today magnetic resonance imaging (MRI) is a reliable technique to study neurovascular interaction at the trigeminal root entry zone [64,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] and it must be performed in every TN patient candidate to MVD. Meaney et al [86], sustaining that MRI is "an extremely sensitive and specific method for demonstrating vascular compression in TN", concluded that "open surgical procedures can be recommended with confidence".…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…At operation, Tew et al [60] found a "significant" impingement in less than half of 50 patients in whom preoperative study showed arterial loop and neurovascular contact. Fortunately, today magnetic resonance imaging (MRI) is a reliable technique to study neurovascular interaction at the trigeminal root entry zone [64,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] and it must be performed in every TN patient candidate to MVD. Meaney et al [86], sustaining that MRI is "an extremely sensitive and specific method for demonstrating vascular compression in TN", concluded that "open surgical procedures can be recommended with confidence".…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Symptomatic NVC is often found at the affected trigeminal nerve, but asymptomatic NVC is also detected at the contralateral and normal trigeminal nerves. 3,4,6 Regarding the MR imaging findings of the NVC, it remains to be clarified whether the NVC by an artery or a vein at the trigeminal nerve root entry zone causes TN.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent advances in MR imaging have provided us with fine volumetric data regarding the anatomic elements composing the NVC. [3][4][5][6][7][8][9][10][11][12] NVC is often detected on the affected side of TN (affected trigeminal nerve), though it is not infrequently observed in the asymptomatic nerve contralateral to the affected side (contralateral trigeminal nerve), as well as in the normal trigeminal nerve in a control subject without TN (normal trigeminal nerve). 3,4,6 The significance of the MR imaging findings of the NVC has not been established, and it remains unclear whether the NVC is symptomatic and linked to cause TN or asymptomatic and observed incidentally.…”
mentioning
confidence: 99%
“…Cependant la décompression vasculaire chirurgicale entraîne dans la majorité des cas une rémission de la douleur qui plaide en faveur de cette étio-pathogénie. Différents auteurs [9,1] ont mis en évidence selon des critères neuroradiologiques, par des techniques de tomographie par résonance magnétique tridimensionnelle, et par angiotomographie à haute définition par résonance magnétique, des corrélations entre l'intensité de la douleur et l'interaction neurovasculaire. Une image radiologique de compression ou de dislocation d'un nerf par une artère est toujours associée à des symptômes de névralgie trigé-minale, alors qu'un simple contact entre un vaisseau et un nerf n'est pas spécifiquement responsable d'une symptomatologie.…”
Section: Commentairesunclassified
“…Le statut de la névralgie trigéminale essentielle ou idiopathique s'est trouvé largement remis en cause au cours des 30 dernières années par l'amélioration des moyens d'imagerie [1] et les résultats des interventions neurochirurgicales [2] de la fosse cérébrale postérieure qui ont abouti à la résolution spectaculaire d'un grand nombre de conflits vasculo-nerveux. Cette résolution chirurgicale s'accompagne très régulièrement d'une amélioration, voire de la disparition totale des douleurs [3] , qui font douter de l'opportunité de maintenir une séparation étanche entre névralgie «symptomatique» et névralgie dite essentielle parce qu'on n'a pu jusqu'ici identifier sa cause.…”
unclassified